EDUCATION ON THE DANGERS OF DRUGS AND ALCOHOL AS AN EFFORT TO STRENGTHEN STUDENT CHARACTER AT SMPN 3 PAMARAYAN - Ende, Ende; Ezcky Satria; Aisyah Nur Salsabila; Elsa Merinda Isabela; Sheima Oktaviani; Novinda Rinjani (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Drug and alcohol abuse among adolescents poses a serious threat to their health, academic performance, and psychosocial development. The focus of this community service program is to increase the knowledge and preventive attitudes of students at SMPN 3 Pamarayan regarding the dangers of drugs and alcohol. The subjects of the activity are 50 students in grades VIII–IX, assisted by the principal, guidance counselors, and Babinsa Polsek Pamarayan as facilitators. The objective of the community service program is to increase understanding and shape preventive behavior among students through a community action-based approach. The methods used included interactive counseling, discussions, and pre- and post-evaluations. The results of the activity showed significant Keywords: Education, Drugs and Alcohol